Epidemiologic characteristics of leprosy in Mainland China, 2004–2020 - Yang, Yuanchao; Zeng, Jiaqi; Li, Jingyi (Frontiers in Public Health, 2025)
BackgroundLeprosy is a chronic infectious disease caused by Mycobacterium leprae. This study aimed to elucidate the epidemiological characteristics of this condition in China from 2004 to 2020.MethodsNew leprosy case and incidence data covering all 31 provinces in Mainland China from 2004 to 2020 were collected from the Data Center of China’s Public Health Science. The temporal, regional, and age-specific distributions of leprosy were analyzed through epidemiological methods.ResultsFrom 2004 to 2020, a total of 5,478 leprosy cases were reported in China, with an average annual incidence rate of 0.0239 per 100,000 population, which indicates a low and stable endemicity. Geographically, the highest disease burden was observed in Yunnan, Guangdong, Sichuan, Guizhou, and Guangxi provinces. Regarding age distribution, the majority of cases were observed among individuals aged 30–49 years (2,171 cases, 39.63%), and the highest incidence rate was found in the 60–69-year age group.ConclusionLeprosy incidence remained stably low nationwide and displayed significant regional variation. New cases clustered predominantly in Southwestern and Central–South China (Yunnan, Guangdong, Sichuan, Guizhou, and Guangxi). The disease burden showed distinct age patterns, with the highest case numbers detected in middle-aged adults and peak incidence rates in the older population. Targeted prevention strategies should prioritize these high-burden regions and peak-affected age groups.